AGW610 - Finance And Accounting For Management - August - September 1998 - PPP, Pusat Pengajian Pengurusan (1998)
UNIVERSITI SAINS MALAYSIA Master of Business Administration First Semester Examination Academic Session 1998/99 August/September 1998 AGW610 - Finance And Accounting For Management Time: [3 hours] INSTRUCTIONS: Please make sure that this examination paper consists of SEVEN (7) printed pages before you begin. Answer any FIVE questions.